UJI ANATOMI DAN MOLEKULER SANSEVIERIA TRIFASCIATA - Whika Febria Dewatisari (LPPM Universitas Terbuka, 2010)
Sansevieria is an ornamental plant which has variation leaves on colour and form. It has unstabilizaton characteristic of genetic. This condition especially happens on species Sansevieria trifasciata. Sansevieria trifasciata which has been expressed to the colour and form of leaves. Variation in isozyme banding pattern knew morpholog variation in species S. trifasciata. The aim of this research looked at difference of anatomycal structure for organs, and any variation in their isozyme banding pattern of S. trifasciata Green tiger, Hahnii medio picta, Green arrow, Golden hahnii, serta Hahnii cream. The approach were used morphology and microscopic observation of surface leaf, stalk, and root organs; isozyme banding pattern used electrophoresis method. The genetic diversity knew from the analyze result of isozyme based on the matric of genetic distance which applied on the shape of dendogram with Hierarchical Cluster Analysis metode average linkage (between groups) program SPSS 14. The results showed that genetic diversity of S. trifasciata Hahnii cream, Green arrow, Hahnii medio picta, Golden hahnii, and Green tiger have been found. Morphology observations, there was a unique character on S. trifasciata Hahnii medio picta,while the microscopic observation on leaves organ, all varieties have the same form, Green arrow has different on stalk cells compared with the others varieties. Root cells of Golden Hahnii and Hahnii cream have same cell. The dendogram resulting from peroxydase data of S. trifasciata was clustered in two groups while S. trifasciata Hahnii medio picta has own character in group. Accordingly the esterase data showing it divided two group, S. trifasciata Golden hahnii has own character.